Análisis de factibilidad para la creación de un sistema para el control y seguimiento a los docentes en sus clases virtuales sincrónicas y asincrónicas en la Unidad Educativa 23 de Junio del Cantón Baba - Moyano Oquendo, Degni Elizabeth (2020)
The present case study has as its main objective the feasibility analysis for the creation of a control and monitoring system for teachers in their synchronous and asynchronous classes of the educational unit "June 23" of the Baba canton. It is aimed at solving a problem which is of great importance in this era of covid-19, as is education, so it is necessary to create a computer system capable of streamlining and optimizing the control processes for teachers. This system is capable of registering the teachers of the institution, records their attendance automatically when entering the system, in addition to the fact that the teachers will be able to record the activities they perform daily, the schedules are stored in the system to remind them of the course they have to teach, among other functional requirements. It was possible to determine that the system is feasible to control and monitor both the teacher and the subject in a satisfactory way, it is very easy to handle so that they do not have complications when entering. In addition to having an economic price for its development and implementation.